Feasibility, safety and clinical efficiency of optometric service pathways at primary and tertiary care level in ampang, malaysia: A pilot study - Hussin D.A.; Hendicott P.; Carkeet A.; Baker P.; Chen A.-H.; Asnir Z.Z.; Abidin Z.Z.; Hussain R.; Mokhtar A. (Kugler Publications, 2024)
Indexed by SCOPUS/ERA